A unique blend of interpersonal and transactional strategies in English email responses to customer complaints in a B2C setting: A move analysis. (January 2022) - Van Herck, Rebecca; Decock, Sofie; Fastrich, Bridgit
Abstract: Although many studies have conducted a move analysis of customer service genres (e.g., responses to online negative reviews), no previous study has investigated the discourse structure of organizational email responses to customer complaints in a business-to-consumer context. This is surprising because email is one of the preferred channels for complaint handling by companies and consumers. We address this gap by performing a move analysis to look into rhetorical and linguistic patterns of this genre and by comparing it to related customer service genres. To achieve these two goals, we used an authentic data set of 150 English email responses to customer complaints from companies active in the UK. We identified 6 moves and 19 submoves in our sample. The submoves that are prototypical for this sample are (a) the typical submoves: Greeting, Gratitude, Conclusion, and Sign-off/Signature and (b) the conventional submoves: Apology and Explanation . This genre sets itself apart from others as it consists of a unique blend of interpersonal and transactional strategies as a response to negative feedback. This uniqueness highlights the significance of email in service recovery: Companies seem to feel safer to address the transactional dimension in complaint handling via email than via public channels. We recommend customer service agents to use both transactional and interpersonal strategies in company–customer interactions and to avoid standardized, vague, and impersonal realizations of interpersonal moves. Highlights: Typical submoves are Greeting, Gratitude, Conclusion, and Sign-off/Signature. Conventional submoves are Apology and Explanation. The genre contains a unique mix of interpersonal and transactional moves. Service agents do not seem to exploit the chance to foster customer relationships. This genre is part of a genre colony: organizational responses to customers.